Understanding domestic air-conditioning use behaviours: Disciplined body and frugal life. (February 2017) - Gou, Zhonghua; Lau, Siu-Yu Stephen; Lin, Pingying
Abstract: Air-conditioning is more and more popularly used in domestic environments. The current understanding of using air-conditioning is based on technocracy of physiological thermal comfort, while ignoring socio-economic contexts. Taking Hong Kong as an example, this article aims to construct a non-technocratic understanding of air-conditioning uses in a relation to the housing status and demographics. This article argues that domestic air-conditioning is being used in order to dress appropriately and to forbid body sweating and odours during dining, sleeping and family gathering. The difference of air-conditioning use intensity is largely attributed to the disparity of economic status. Residents in public rental housing or with lower household incomes tended to have more frugal habits of using air-conditioning to rebate energy expenditure. Disciplined body and frugal life are proposed in this article to more critically expound the signification of air-conditioning in residential environments. A non-technocratic understanding of air-conditioning can bring forth better solutions to enhancing quality of life. Highlights: Technocratic understanding air-conditioning is criticised. A household survey is presented to understanding domestic air-conditioning uses. Air-conditioning is not rational to thermal comfort or thermal performance. Disciplined body and frugal life are proposed to understand the use behaviours. Non-technocratic understanding can lead to better solutions to enhancing quality of life.